2011
DOI: 10.1042/bj20102057
|View full text |Cite
|
Sign up to set email alerts
|

TFCP2c/LSF/LBP-1c is required for Snail1-induced fibronectin gene expression

Abstract: Fibronectins are cell-secreted glycoproteins that modulate cell attachment, spreading, migration, morphology, differentiation and oncogenic transformation. Fibronectin expression is activated during EMT (epithelial-mesenchymal transition) and is a hallmark of mesenchymal cells. It is shown in the present study that a transcription factor previously unrelated with EMT, TFCP2c/LSF/LBP-1c, was translocated to the nucleus and bound to the fibronectin promoter upon EMT induction by Snail1. Consequently, the interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Our findings also showed that the core promoter was found from the human FN1 promoter region (−2000 to +200), and contained the putative regulatory motifs (CNRG-N 5–6 -CNRG/C). Inconsistent with the previous report [ 13 ], we found the TFCP2 regulation on FN1 through the same motifs. This further illustrates that TFCP2 regulates FN1 across different cell systems.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings also showed that the core promoter was found from the human FN1 promoter region (−2000 to +200), and contained the putative regulatory motifs (CNRG-N 5–6 -CNRG/C). Inconsistent with the previous report [ 13 ], we found the TFCP2 regulation on FN1 through the same motifs. This further illustrates that TFCP2 regulates FN1 across different cell systems.…”
Section: Discussionsupporting
confidence: 89%
“…This further illustrates that TFCP2 regulates FN1 across different cell systems. Porta-de-la-Riva et al [ 13 ] found that FN1 was up-regulated upon EMT induction by Snail1 in normal development, then TFCP2 was found to bind the FN1 proximal promoter, which responses to Snail1. In our paper, FN1 was selected from ChIP on chip and array results of TFCP2 in cancer (HCC), we used a series of 5′-deletion fragments of the FN1 promoter (~2 kb region) to locate the responsive minimal promoter to TFCP2 and found involvement of TFCP2 in migration, as mediated through its direct upregulation of FN1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three SNPs (rs35244636, rs116716037, and rs113859079) present in the human WISP1 promoter could alter putative transcription factor binding site, and rs35244636 also could result in the loss of a predicted TFCP2 binding site. Previous studies indicate that TFCP2 can be activated by secreted phosphoprotein 1 (38), activates fibronectin promoter upon epithelial-mesenchymal transition (EMT) induction by snail homolog 1 (Snail1) (39), and enhances angiogenesis by transcriptional activation of matrix metalloproteinase 9 (40) that modulates matrix turnover and inflammation in VILI (41,42). Accordingly, we pursued WISP1 protein in further detail in the current study on VILI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Third, LSF overexpression can contribute to chemoresistance [ 7 ], since LSF transcriptionally regulates expression of thymidylate synthase [ 10 ], a target of the chemotherapeutic agent 5-fluorouracil [ 7 ]. Finally, nuclear translocation of LSF upon overexpression of Snail can lead to transcriptional upregulation of fibronectin expression, contributing to induction of the epithelial-mesenchymal transition (EMT) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%